PENERAPAN STANDAR PEMBINAAN PESERTA DIDIK MELALUI KURIKULUM BERBASIS NILAI-NILAI ISLAM DI SDIT KAUTSAR ILMI - Merri Yelliza (STKIP Subang, 2025)
Character education plays a crucial role in shaping the personality of students, particularly at the elementary education level. This study aims to explore the implementation of a character-based curriculum at SDIT KAUTSAR ILMI, which integrates Islamic values in both academic learning and extracurricular activities. A qualitative descriptive approach with a case study design was used, involving in-depth interviews, observations, and documentation as data collection methods. The findings show that integrating Islamic values across various subjects and extracurricular activities at SDIT KAUTSAR ILMI positively impacts the development of students' character, focusing on honesty, discipline, responsibility, and empathy. However, challenges such as time limitations, resource constraints, and a lack of teacher training were identified. In conclusion, while the character-based curriculum at SDIT KAUTSAR ILMI has significantly contributed to students' development, improvements in teacher training and resource availability are necessary to optimize its implementation.